Energetic neutral N2 atoms treatment on the kithul (Caryota urens) starch biodegradable film: Physico-chemical characterization. (June 2020) - Sudheesh, Cherakkathodi; Sunooj, Kappat Valiyapeediyekkal; Sasidharan, Abhilash; Sabu, Sarasan; Basheer, Aaliya; Navaf, Muhammed; Raghavender, Chikkonda; Sinha, Suraj Kumar; George, Johnsy
Abstract: The effect of energetic neutral nitrogen atoms (ENA) treatment at different plasma power (5 W, 10 W, 15 W and 20 W) for 10 min on the physico-chemical, mechanical, barrier and thermal properties of kithul starch films were studied. The surface of kithul starch film after ENA treatment showed higher roughness. Energetic neutral nitrogen atom treatment increased crystallinity. Tensile properties significantly (p ≤ 0.05) increased after ENA treatment. Water vapour permeation (WVP), oxygen permeability, solubility and moisture absorption decreased in ENA treated kithul starch films. Higher opacity and lower WVP and oxygen permeability confirmed better barrier properties of ENA treated kithul starch films. Hence, treated kithul starch films with improved mechanical and barrier properties have a potential role in the area of biodegradable films. Graphical abstract: Image 1 Highlights: Kithul starch films treated with energetic neutral nitrogen atoms showed higher roughness. 20W-10 min treated kithul starch film showed highest relative crystallinity. Tensile properties increased after energetic neutral nitrogen atoms treatment. Hydrophobic properties increased after energetic neutral nitrogen atoms treatment.